Into a rhythm: diel activity patterns and behaviour in Mediterranean slipper lobsters, Scyllarides latus. (30th January 2015) - Goldstein, Jason S.; Dubofsky, Elizabeth A.; Spanier, Ehud
Abstract: Although the natural history for Mediterranean slipper lobsters ( Scyllarides latus ) is well established, there exists a disproportionate lack of important biological and physiological data to verify many key traits, including to what extent endogenous rhythms modulate aspects of their behaviour. Although Scyllarids appear nocturnally active, few studies exist that quantify this tendency. Our overall objective was to test the hypothesis that adult slipper lobsters are nocturnal and to determine if their diel activity rhythms are under the influence of an endogenous circadian clock. In the laboratory, we exposed a total of 16 animals ( CL avg = 92.6 ± 6.6 mm; CL, carapace length) to a 12 : 12 light : dark (LD) cycle for 7–10 d, followed by ***constant dark (DD) for 15–20 d. Activity was assessed using a combination of time-lapse video and accelerometers. Of a total of 16 lobsters, we analysed data from 15 (one mortality). All 15 lobsters were evaluated using video. Thirteen of these lobsters were also evaluated using accelerometers. All lobsters were more active during night-time than during daytime and synchronized their activity to the LD cycle, expressing a diel activity pattern ( τ = 24.04 ± 0.13 h). In DD, lobsters maintained a circadian rhythm with a τ of 23.87 ± 0.07 h. These findings may provide insight into the behaviour of these animals in their natural habitat and help explain their ability to anticipate dawn and dusk.